2021
DOI: 10.1088/1755-1315/741/1/012033
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Biochar and Manure on Some Soil Characteristics and Growth of Garlic [Allium Sativum L.] on Ultisols

Abstract: Ultisol is a soil type having high clay content and low OM, therefore it has limited aeration and drainage. Generally, the soil is not conducive for plant growth, especially for tuber crops. Organic matter is known as a soil ameliorant because it can improve soil’s physical, chemical, and biological properties. Besides manure having widely used, another OM source is biochar which can stay for a long time in soil. This research was aimed to improve the soil properties of Ultisols and the growth of garlic [Alliu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
2
4
0
Order By: Relevance
“…decreasing soil BD caused the TSP increased. As reported before that biochar application on Ultisols decreased the soil BD and increase the TSP [3].…”
Section: Correlation Between Som and Other Soil Physical Propertiessupporting
confidence: 80%
See 2 more Smart Citations
“…decreasing soil BD caused the TSP increased. As reported before that biochar application on Ultisols decreased the soil BD and increase the TSP [3].…”
Section: Correlation Between Som and Other Soil Physical Propertiessupporting
confidence: 80%
“…It increased soil total soil porosity (TSP) by 66%, hydraulic conductivity rate 603%, water content at field capacity (pF 2.54) by 24%, and plant available water by 89%, as well as decreased the soil bulk density (BD) by 34% and soil water content at wilting point (pF 4.2) by 4.6% by increasing biochar application up to 1.5% on weight basis compared to control (0% biochar application). Application of biochar was also reported to increase soil OC as well as soil N and P of Ultisol [3]. Solfianti et al [9] also found increasing CEC, basic cations especially Ca, Mg, and K besides OC and pH of Inceptisols after biochar application up to 20 T/ha.…”
Section: Other Soil Physical Propertiesmentioning
confidence: 90%
See 1 more Smart Citation
“…Another amendment material that is quite popular lately is biochar. Biochar could improve soil chemical properties (Yulnafatmawita et al 2020;Ethik et al 2021;Solfianti 2021), soil biological properties (Dermiyati et al, 2017;Nurbaity et al, 2019), and soil physical properties (Yulnafatmawita et al, 2021;Prakongkep et al, 2021;Gelardi et al, 2021;Fu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For soil physical properties, biochar can increase soil OM content, water retention, and plant available water of fine textured soil (Yulnafatmawita et al, 2021). Biochar has porous structure large specific surface area (Leng et al, 2021;Fu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%